(3cJGH ajeG jLhR ddTGYQ ESJYeGdI aj VQhQI GdTYQ Ydi fSb GdCdbGHs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje QH CfYeJ aRO gPG cJGH fPcQ ajg eG jLhR ddTGYQ ESJYeGdI ai VQhQI GdTYQ Ydi fSb GdCdbGH GdPi VefgG UGMH GdLed GdHGH GdPi PcQgG ajg eLedI djchf gPG GdcJGH TQMkG dgPG GdHGH s
(3BNQgG (B:s
(3EfeG ETJQWfG GdCdbGH GdJi PcQgG UGMH GdLed eLehYI ai GdHGH GdPi bOefG PcQg hbO JeJ CdbGHg hCJeefG fMf TQMgG HGdJYdjd hGdJeKjd hGdMeO ddg Ydi Yhfg hJCjjOg Je GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf L(B1 (3U` (B603 (3Cf cJGH GdLed dCHh GdbGSe GdRLGLi GdfMhi s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs